The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00277-014-2207-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mast cell leukemia (MCL) with KIT S476I: a rare entity defined by leukemic expansion of mature mast cells and absence of organ damage

Abstract: Mast cell leukemia (MCL) is a rare, life-threatening malignancy defined by a substantial increase in neoplastic mast cells (MCs) in bone marrow (BM) smears, drug-resistance and a poor prognosis. In most patients, the survival-time is less than 1 year. However, exceptional cases may present with a less malignant course. We report on a 49-year-old female patient with MCL Europe PMC Funders Group Europe PMC Funders Author ManuscriptsEurope PMC Funders Author Manuscripts diagnosed in 2013. In February 2013, firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…In our series, the proposed subtypes of MCL without C-findings (chronic MCL) and leukemic MCL were only observed in 2 patients each, in line with previously published series, 14 , 15 the latter clearly demonstrating that presence or absence of MCs in PB is only of minor importance for the diagnosis of MCL. We have, however, observed a much higher relative frequency of MCL-AHN than that reported in the literature (71% vs .…”
Section: Discussionsupporting
confidence: 92%
“…In our series, the proposed subtypes of MCL without C-findings (chronic MCL) and leukemic MCL were only observed in 2 patients each, in line with previously published series, 14 , 15 the latter clearly demonstrating that presence or absence of MCs in PB is only of minor importance for the diagnosis of MCL. We have, however, observed a much higher relative frequency of MCL-AHN than that reported in the literature (71% vs .…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the KIT mutation is the most important and prevalent pro-oncogenic mutation in MCL. In this study, we found the presence of a KIT S476I mutation, which has been discovered previously in chronic MCL [ 15 ]. With our finding, this point mutation becomes the second most common point mutation in MCL, following KIT D816V, which is located in the tyrosine kinase domain.…”
Section: Discussionsupporting
confidence: 77%
“…Almost 40% of de novo patients with MCL had the KIT D816V mutation [ 1 ]. In addition, S476I, F522C, V654A, V560G, duplication of amino acids 501–502 and 502–503, and deletion of amino acids 501–502 were also reported in a case report [ 10 11 12 13 14 15 ]. Besides the KIT mutation, a TET2 mutation has been investigated in aggressive SM [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
“…2 Chronic MCL is defined as MCL without C-findings/organ damage and may display a more indolent course over time, but its natural history requires more study. [24][25][26] Immunostaining with Ki-67 has been shown to differentiate between the acute and chronic variants, since most mast cells in chronic MCL stain negative for Ki-67 whereas mast cells in acute MCL frequently display Ki-67. 24 These findings require validation in additional studies.…”
Section: Mast Cell Leukemiamentioning
confidence: 99%
“…In some cases, organdirected biopsy may be useful to determine whether organ damage is related to the SM or AHN or both (eg, liver biopsy in a patient with liver function abnormalities). Although chronic MCL may follow a more indolent disease course compared with acute MCL with organ damage, [24][25][26] cytoreductive therapy should still be considered for such patients given the poor prognosis of both MCL subtypes (see "Treatment for MCL," page 1509, [SM-8]).…”
Section: Treatment Considerationsmentioning
confidence: 99%